Selenium Supplementation Tended to Increase Digestibility and Milk Fat Content in Dairy Goats: A Meta-Analysis - Nurmala, D. P.; Susilorini, T. E.; Sjofjan, O.; Adli, D. N. (Faculty of Animal Science, IPB University, 2024)
A meta-analysis was conducted to determine the effects of selenium supplementation on milk production, milk composition, and nutrient digestibility in dairy goats. A database was constructed based on relevant published papers. Related studies that met the criteria were sourced from PubMed, Scopus, and Google Scholar. After the identification of studies through the SYRCLE method, the final dataset consisted of 15 studies and 188 treatments. The data were analyzed using R version 4.3.3 (2024-02-29 ucrt) “Angel Food Cake”, which utilizes packages such as lme4, lmerTest, and caret. The results showed that increasing concentrations of selenium tended to increase the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), and total digestible nutrients (TDN) (p<0.05). Additionally, the results indicated a significant improvement on the milk fat content (p<0.05). In conclusion, selenium supplementation until 0.2 mg/kg significantly increase digestibility and milk fat content in dairy goats.